Transcatheter closure of ventricular septal defect from retrograde transarterial approach: immediate and long-term outcome - Fatema, Nurun Nahar (International Journal of Contemporary Pediatrics, 2020)
Background: Ventricular septal defect (VSD) is a commonly encountered congenital heart defect. The aim of this study was to analyze five years’ experience with patients who had undergone transcatheter closure of VSD using retrograde transarterial approach. Methods: It was a retrospective study conducted from December 2014 to December 2019. Cases planned for VSD closure in retrograde approach were included. A total of 147 cases fulfilled the criteria after left ventricular angiography and procedure was performed without forming arteriovenous loop. Follow up was planned at 1, 3, 6, 12 months and yearly thereafter. Results: The mean age of the patients was 5.94±4.67 years and mean weight was 17.93±8.26 kg. Perimembranous VSD was present in 70.06% cases and the size of the VSD was 5.5±1.8 mm. Amplatzer duct occluder II was the commonest device used (55.24%). Mean device size was 6.2±1.8 (5-8 mm). Complete occlusion was achieved immediately in 94.56% cases, and after one month in 99.36% cases. Four (2.78%) cases were postponed for malpositioning and encroachment of aortic valve. One patient (2.22%) had tiny residual VSD up to 3 years follow up. Bacterial endocarditis was noticed in one patient (0.80%) at one year follow up. No evidence of complete heart block was encountered in follow up period of six to 60 months. Conclusions: This study recommends that retrograde transarterial approach for closure of moderate to small VSD is safe, effective, and minimally invasive, can be performed in short time with less radiation hazard and less trauma to conducting tissues.